EFFECT OF SUPPLEMENTATION OF DIFFERENT LEVELS OF DRIED TAMARIND PULP ON MEAT CHOLESTEROL, CARCASS YIELD, DRESSING PERCENTAGE AND ABDOMINAL FAT OF BROILER CHICKEN - Shinde, GB; Kanduri, AB; Patil, PV; Pawar, PH (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
The present study was conducted to investigate the effect of supplementation of different levels of dried Tamarind pulp on meat cholesterol, carcass yield and dressing percentage of broiler chicken. 300 healthy day old commercial broiler chicks of Vencob’ strain were selected and divided into five groups of 60 chicks in each group, three replicates of 20 birds in each group. The chicks of control group (Group I) were fed with standard broiler diet without dried Tamarind pulp, whereas dried Tamarind pulp was supplemented @250 gm, 500 gm, 1000 gm and 1500 gm per 100 kg of broiler ration respectively to groups -II, III, IV and V.The meat cholesterol was found to be significantly lower in treatments groups than in control group. However, carcass yield and dressing percentage of treatment groups were significantly higher than control Group.The carcass yield and dressing percentage were increased and meat cholesterol level was decreased on supplementation of dried Tamarind pulp in broiler rations.
Keywords: Dried Tamarind pulp; Broiler chicken; Carcass yield; Dressing percentage; Meat Cholesterol